Tackling the COVID-19 pandemic: Initial responses in 2020 in selected social health insurance countries in Europe☆. Issue 5 (May 2022) - Schmidt, Andrea E.; Merkur, Sherry; Haindl, Anita; Gerkens, Sophie; Gandré, Coralie; Or, Zeynep; Groenewegen, Peter; Kroneman, Madelon; de Jong, Judith; Albreht, Tit; Vracko, Pia; Mantwill, Sarah; et al.
Highlights: Social health insurance funds had no major role in managing COVID-19. Responsibility shifted towards central government and away from SHI funds. Decentralised pandemic management may cause coordination costs Coordinated ambulatory care often helped avoid overburdening hospitals. Providers increasingly used teleconsultations, which may remain part of standard practice. Abstract: Countries with social health insurance (SHI) systems display some common defining characteristics - pluralism of actors and strong medical associations - that, in dealing with crisis times, may allow for common learnings. This paper analyses health system responses during the COVID-19 pandemic in eight countries representative of SHI systems in Europe (Austria, Belgium, France, Germany, Luxembourg, the Netherlands, Slovenia and Switzerland). Data collection and analysis builds on the methodology and content in the COVID-19 Health System Response Monitor (HSRM) up to November 2020. We find that SHI funds were, in general, neither foreseen as major stakeholders in crisis management, nor were they represented in crisis management teams. Further, responsibilities in some countries shifted from SHI funds to federal governments. The overall organisation and governance of SHI systems shaped how countries responded to the challenges of the pandemic. For instance, coordinated ambulatory care often helped avoid overburdening hospitals. Decentralisation among local authorities may however represent challenges with the coordination of policies, i.e. coordination costs. At the same time, bottom-up self-organisation of ambulatory care providers is supported by decentralised structures. Providers also increasingly used teleconsultations, which may remain part of standard practice. It is recommended to involve SHI funds actively in crisis management and in preparing for future crisis to increase health system resilience.